(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
The paper discusses the elaboration of new study program and curricula in Environmental Engineering at the Rezekne University (RU).The main goal of the Program is to prepare new formation of Environmental specialists - Ecotehnblogists, who are able not only to control pollution of Enviroment, but to prevent it on the early stages by applying in industry ecologically safe technologies.